The incidence of tuberculosis in the municipality of Santana do Ipanema during 2016 and 2017 - Janilo Italo Melo Dantas; Itamara Thuane Conceição Costa (Universidade Estadual de Alagoas, 2020)
Tuberculosis is an infectious disease caused by Mycobacterium tuberculosis, with direct transmission. It is concentrated as one of the main diseases that has affected the health of individuals worldwide, from ancient times to the present. In view of its dissemination, there have been many collective government actions aimed at combating its incidence in different populations, however, despite many preventive actions, it still becomes one of the main diseases that needs to be controlled in several regions of the country, due to the existence of mortality and morbidity that it has caused. In view of this, this study aimed to identify the incidence of tuberculosis in the municipality of Santana do Ipanema, during the years 2016 and 2017. For data collection, consultations were carried out on platforms of the municipal health secretariat of the municipality of Santana do Ipanema, and on the DATASUS website, discussing case numbers with the multiprofessional health team. A total of 28 new cases of tuberculosis were identified in the municipality between the years 2016 to 2017, a number considered low when compared to other regions of the state, however, the number of patients abandoning treatment of the disease was equivalent to 60%, making it necessary to raising awareness of its treatment and prevention, since its treatment requires extensive continuity so that it can be carried out effectively.